Social vulnerability and cardiovascular risk factors in adolescents - Viviane Freire de Farias; Larissa Almenara Soares; Luciana Nicolau Aranha; Ronir Raggio Luiz; Gláucia Maria Moraes de Oliveira; Glorimar Rosa (BMC, 2024)
Abstract Background Social vulnerability can influence in the development of cardiovascular risk factors in adolescents (CRF). For this reason, the objective of our study was to evaluate the presence of CRF in adolescents, according to social vulnerability. Methods This is a cross-sectional study with 517 adolescents of both sexes, from 10 to 19 years of age, classified into 2 groups by social vulnerability, according to socioeconomic characteristics collected by means of questionnaires, where adolescents who did not have access to drinking water, sewage network, and adequate per capita income were classified as vulnerable. Anthropometric, biochemical, and blood pressure data were evaluated. Level of physical activity was assessed by an adapted questionnaire, and food intake was assessed by a 3-day food record. Independent T, Mann-Whitney, and χ2 tests were used, according to the scale of measurement of the variables, on the statistical program SPSS, version 25, at a significance level of 5%. Results Adolescents had median age of 14 (11 to 15) years; 58.4% were female; 32.4% were overweight, and 52.4% were physically inactive in leisure. Mean consumption of ultra-processed food was observed to account for 45.0% of calorie intake. Adolescents classified as vulnerable had lower weight, body mass index, waist circumference, hip circumference, and neck circumference when compared to non-vulnerable adolescents. Both groups had cholesterol concentrations above the normal level. Non-vulnerable adolescents had higher triglyceride concentrations, higher alcohol consumption, and lower fiber intake compared to vulnerable adolescents. Conclusions Adolescents with social vulnerability are less likely to have cardiovascular risk factors.